Las inteligencias múltiples y la importancia del desarrollo de la inteligencia emocional - Irrazabal B., Alexandra; Solano Sisalima, Gabriela; González Orbea, Gardenia Leonor; Centeno Suarez, Carmen; Segarra Mendoza, Rosa Esther; Gina Janeth Vargas vera, Gina Janeth (Revista Minerva, 2024)
Child development is crucial in the formation of cognitive, emotional and social skills that last throughout life. This article explores how Howard Gardner's theories of multiple intelligences and Daniel Goleman's emotional intelligence can be integrated to promote comprehensive development in children. The aim of the study is to assess how these theories can be combined in educational practices to foster more balanced and equitable development. The research employs a mixed methodological design, combining qualitative and quantitative methods, to gain a more complete understanding of the impact of multiple intelligences and emotional intelligence on child development. The results of the study will be thoroughly analysed, highlighting differences in participants' multiple intelligences and emotional intelligence levels, as well as their experiences and perceptions. These findings will provide a comprehensive view of child development and highlight the importance of considering both cognitive and emotional skills in education. This study seeks to contribute to knowledge about child development by demonstrating how a combination of theoretical approaches can support more inclusive and effective learning and development, addressing the diverse strengths and needs of each child. As a result, by considering both multiple intelligences and emotional intelligence, a solid foundation is provided for implementing educational practices that promote comprehensive and equitable development in children.
Keywords: Child development, emotional, Cognitive, emotional skills, Self-awareness, Self-regulation, Motivation, Education